Toronto’s Nineteenth-Century Exhibition Parks: “...free of admission to all peaceable persons...” - Bain, David (Ontario History)

(untitled) (The Ontario Historical Society, 2022)
Toronto’s two Exhibition Parks were set aside for an exhibition and for various other fairs and shows. However, when the site would otherwise have been empty and barren, the space and buildings could be used and appreciated by the entire community. This could be rationalized as a way to justify the use of public money to support an expensive private enterprise. This article has three goals: to determine how successful this arrangement was; to examine the history and character of the two parks in the nineteenth and early twentieth centuries; and to examine how the parks were developed and altered in search of a balance between the private and public sectors. In the conclusion, examples from elsewhere in Canada will be used to offer some comparisons and contrasts to Toronto’s experience.